Induction of T helper type 1 and 2 responses to 19-kilodalton merozoite surface protein 1 in vaccinated healthy volunteers and adults naturally exposed to malaria. - Lee, E; Palmer, DR; Flanagan, K; Reece, W; Odhiambo, K; Marsh, K; Pinder, M; Gravenor, M; Keitel, W; Kester, K; Diggs, C; Kaslow, D; et al. (2002)
Plasmodium falciparum malaria is a major cause of death in the tropics. The 19-kDa subunit of P. falciparum merozoite surface protein 1 (MSP-1(19)), a major blood stage vaccine candidate, is the target of cellular and humoral immune responses in animals and humans. In this phase I trial of MSP-1(19), immunization of nonexposed human volunteers with either of the two allelic forms of recombinant MSP-1(19) induced high levels of antigen-specific Th1 (gamma interferon) and Th2 (interleukin 4 [IL-4] and IL-10) type lymphokines. The adjustment of the antigen dose and number of immunizations regulated the level of specificity of immune responses and Th1/Th2 bias of responses induced by vaccination. Novel conserved and allelic T-cell epitopes which induced cross-strain immune responses were identified. Importantly, responses to many of these novel epitopes were also present in adults exposed to malaria, both in east (Kenya) and west Africa (The Gambia). These data suggest that epitope-specific naturally acquired MSP-1(19) immune responses in endemic populations can be boosted by vaccination.